Anonymous Trading in Equities - MELING, TOM GRIMSTVEDT (Journal of Finance, 2021)
ABSTRACT In this paper, I explore a reform at the Oslo Stock Exchange to assess the causal effect of posttrade trader anonymity on stock liquidity and trading volume. Using a regression discontinuity approach, I find that anonymity leads to a reduction in bid‐ask spreads of 40% and an increase in trading volume of more than 50%. The increase in trading volume is accounted for largely by increased trading activity by institutional investors, while retail investors do not adjust their trading behavior in response to anonymity. The results suggest that posttrade anonymity positively affects standard measures of market quality.